Hematopoietic activity of human short-term repopulating cells in mobilized peripheral blood cell transplants is restricted to the first 5 months after transplantation - Zavidij, Oksana; Ball, Claudia R.; Herbst, Friederike; Fessler, Sylvia; Schmidt, Manfred; Kalle, Christof von; Glimm, Hanno (Blood, 2010)
Kinetics of hematopoietic recovery driven by different types of human stem and progenitor cells after transplantation are not fully understood. Short-term repopulating cells (STRCs) dominate early hematopoiesis after transplantation. STRCs are highly enriched in adult mobilized peripheral blood compared with cord blood, but the length of their contribution to hematopoiesis remains unclear. To understand posttransplantation durability and lineage contribution of STRCs, we compared repopulation kinetics of mobilized peripheral blood (high STRC content) with cord blood transplants (low STRC content) in long-lived NOD.Cg-PrkdcscidIl2rgtm1Wjl/SzJ (IL2RG−/−) mice. This comparison demonstrates that quantitative contribution of human STRCs to hematopoiesis is restricted to the first 5 months after transplantation. The ratio of STRCs to long-term repopulating cells dramatically changes during ontogeny. This model enables to precisely determine early and late engraftment kinetics of defined human repopulating cell types and to preclinically assess the engraftment kinetics of engineered stem cell transplants.